2022
DOI: 10.1021/acs.jpclett.2c01596
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Characterization of Dicarbonyls on a RhCu Single-Atom Alloy

Abstract: Dicarbonyl species are ubiquitous on Rh/oxide catalysts and are known to form on Rh+ centers. However, dicarbonyl species have never been directly observed on single-atom alloys (SAAs) where the active site is metallic. Herein, using surface science and theoretical modeling, we provide evidence of dicarbonyl species at isolated Rh sites on a RhCu(100) SAA. This approach not only enables us to directly visualize dicarbonyl species at Rh sites but also demonstrates that the transition between the mono- and dicar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…by performing rigorous control experiments on the monometallic samples. 187 It should be noted that due to the low stability of metal nanoclusters, the activation conditions used before the chemisorption measurements should be carefully selected to avoid sintering or other types of structural transformation of the nanoclusters. Nevertheless, when the probe molecules interact with binuclear bimetallic sites and bimetallic nanoclusters, the adsorption configuration of the probe molecules could be different to the classic metal nanoparticles.…”
Section: Characterization Of Surface Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…by performing rigorous control experiments on the monometallic samples. 187 It should be noted that due to the low stability of metal nanoclusters, the activation conditions used before the chemisorption measurements should be carefully selected to avoid sintering or other types of structural transformation of the nanoclusters. Nevertheless, when the probe molecules interact with binuclear bimetallic sites and bimetallic nanoclusters, the adsorption configuration of the probe molecules could be different to the classic metal nanoparticles.…”
Section: Characterization Of Surface Propertiesmentioning
confidence: 99%
“… Therefore, the precise measurements of the metal sites in bimetallic nanoparticles relies on the identification of the adsorption configuration (mono- or dicarbonyl configuration) of the probe molecule at the measurement conditions (temperature, partial pressure of the probe molecule etc.) by performing rigorous control experiments on the monometallic samples …”
Section: Characterization Of Bimetallic Sitesmentioning
confidence: 99%
“…[7][8][9][10][11][12] Oxidation of CO is a fundamental reaction that plays a critical role in many technologically important systems such as the water gas shift reaction, [13][14][15][16][17][18] catalytic converters, [19][20][21] and for the purification of hydrogen used in proton-exchange membrane fuel cells, [22][23][24][25] In addition, CO is an excellent probe molecule for the characterization of surfaces. [26][27][28][29][30] As a result, the adsorption of CO and its oxidation have been extensively studied in the SAC field. For example, DeRita et al demonstrated that isolated Pt atom active sites can dynamically change under reaction conditions when supported on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, some indications that more than one CO molecule can adsorb on a transition metal substitution atom on a copper surface. Adsorption of two CO molecules has been experimentally observed for Cu surfaces doped with either Co or with Rh, and this has been supported by DFT calculations. This indicates that in order to apply the Sabatier principle correctly and assess the catalytic performance, one needs to consider the adsorption of whatever number of CO molecules is expected to be present under reaction conditions, not just the adsorption of the first CO.…”
mentioning
confidence: 99%